Petanque Sports Coaching Clinic for Physical Education Teachers of Muhammadiyah Senior High Schools and Vocational Schools in Jember Regency - Ahmad Bahriyanto; Agus Prasetyo Utomo; Ahmad Sulaiman; Septanania; Ajodyo Yogo Dwi Pamungkas (Universitas Muhammadiyah Jember, 2025)
Petanque is a relatively new sport in Jember Regency. It is very suitable to be developed in schools because it can be played on the ground, grass or sand measuring 3 x 12 m or 4 m x 15 m. Opportunities for achievement are wide open, both as coaches and athletes because they are relatively new in Jember Regency. In order to spread the petanque sport, training is needed as an introduction to this sport from France. Sports and Health Physical Education Teachers (PJOK) can be pioneers in developing Petanque in schools. PJOK teachers at the Muhammadiyah Senior High School/Vocational/Madrasah Aliyah (SMA/K/MA) in Jember have never known Petanque. Therefore, it is necessary to carry out a coaching clinic. The objectives of this service are, 1) Increasing basic technical knowledge and regulations for the Petanque sport 2) Increasing basic technical skills and training for the Petanque sport. The implementation method is divided into three stages, namely, preparation, implementation and monitoring and evaluation. The preparatory phase includes situation analysis, dialogue with partners, and cooperation agreements. Implementation of the coaching clinic program by presenting theoretical material in class, demonstrations and practice. Monitoring and evaluation is carried out after the training is carried out to find out whether the results of the training are implemented in each school. The dedication carried out by the team resulted in 1) increasing knowledge of the basic techniques of Petanque, 2) Forming a Whatsapp group for PJOK SMA/K Muhammadiyah teachers throughout Jember; 3) Proposal to issue a letter of recommendation by the Head of Elementary and Middle Education (Dikdasmen) Muhammadiyah Regional Leadership (PDM) Jember to school principals containing an appeal to organize the Petanque extracurricular at Muhammadiyah SMA/K/MA schools in Jember.